Resilience and transformation in times of economic crisis: The persistence of community in the Lisbon Metropolitan Area. Issue 5 (20th October 2019) - Carmo, Renato Miguel; Ferreira, Daniela
ABSTRACT: The economic and financial crisis that hit various European countries, including Portugal, has caused a series of social effects and reactions that have been studied using a number of different conceptual approaches. The article looks at two types in particular: those which analyze populations' levels of resilience regarding proximity and community relations; and those which address collective action movements and practices that seek to transform society. The main goal is to consider the fact that these distinct practices coexist in the same territories, suggesting that they should therefore not be analyzed separately. The other objective is to determine what sociological variables and socio-spatial contexts are key to these different types of practices. The study was based on the territory formed by the Lisbon Metropolitan Area (AML) and entailed a survey of 1, 500 of its residents. The data indicate a persistence of proximity and community relations, mainly among residents of rural areas.